2015
DOI: 10.1097/mpa.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2-Angiotensin-(1–7)-Mas Axis Protects Against Pancreatic Cell Damage in Cell Culture

Abstract: ACE2-angiotensin-(1-7)-Mas axis significantly inhibits pancreatitis in response to decreased inflammatory factors by the activation of endothelial nitric oxide synthase and NO signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…The results demonstrated that Ang-(1-7) possessed the potential to inhibit apoptosis and protect the pancreas from damage. These data, together with a previous study (27), demonstrated that exogenous Ang-(1-7) may affect the balance of Ang-(1-7)/Ang II in addition to ACE2/ACE in AP. This is also consistent with previous animal experiments; that identified that ulinastatin significantly ameliorated pancreatic pathology through upregulating ACE2 and Ang (1-7) in addition to the serum biochemistry indicators of CAE-induced SAP mice (28).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results demonstrated that Ang-(1-7) possessed the potential to inhibit apoptosis and protect the pancreas from damage. These data, together with a previous study (27), demonstrated that exogenous Ang-(1-7) may affect the balance of Ang-(1-7)/Ang II in addition to ACE2/ACE in AP. This is also consistent with previous animal experiments; that identified that ulinastatin significantly ameliorated pancreatic pathology through upregulating ACE2 and Ang (1-7) in addition to the serum biochemistry indicators of CAE-induced SAP mice (28).…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have demonstrated that the classic angiotensin-converting enzyme-angiotensin II type 1 receptor (ACE-Ang II-AT1) axis activity increases and may aggravate the development of pancreatitis (12)(13)(14). Studies have demonstrated that ACE2-Ang-(1-7)-Mas [ACE2-Ang-(1-7)-Mas] axis, the non-classical and the depressor renin-Ang system (RAS) pathway, possess adverse effects in numerous diseases and may be therapeutically useful (15,16). However, little is known about the potential roles of ACE2-Ang-(1-7)-Mas in apoptosis, and its precise method of regulation in any organ system.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that Ang 1–7 and its receptor Mas are expressed within AR42J cells ( 6 ). The effect of A779 on CAE-induced TLR4 and NF-κB expression was investigated in AR42J cells pretreated with various concentrations of A779 followed by CAE treatment for 12 h. Relative expression levels of TLR4 and NF-κB were determined by western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Ang 1–7 has been reported to serve as an endogenous antagonist of Ang II, possessing anti-inflammatory and vasodilatory activities, and exerting protective effects against endothelial injury ( 3 5 ). Our previous study revealed that caerulein (CAE) can stimulate the ACE2-Ang-1-7-Mas axis and significantly inhibit pancreatitis development via endothelial nitric oxide synthase activation and nitric oxide signaling within AR42J cells ( 6 ). In addition, further study identified that in the AR42J cells stimulated by CAE, blocking of Mas receptor using A779, then enhancement of Ang ( 1 7 ), still can reduce the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental disease models Ang(1–7)/MAS1 signalling suppress AngII‐induced pathogenesis. For example, AngII‐induced ROS overproduction and apoptosis in cerebral endothelial cells (Xiao et al, ), phosphorylation of c‐Src and MAPKs, leading to production of TGF‐β1 and collagen in cardiac fibroblasts (Meng et al, ; Tao et al, ; Zheng et al, ), muscle atrophy of gastrocnemius (Cisternas et al, ), pancreatic cell damage (Wang et al, ), ICAM‐1, VCAM‐1, and MCP‐1 expression in HUVECs (Liang et al, ,b) is suppressed by Ang(1–7) activated MAS1 receptors.…”
Section: Signallingmentioning
confidence: 99%